Guided inquiry approach a model of integrating environmental education in social studies - Lumbre, Ma. Concepcion B (2007)
This quasi-experimental study determined the effects of guided inquiry model of integration on students' environmental literacy. This research emphasized the need to enhance elementary students' environmental literacy. Integration of environmental concepts in Social Studies is a new dimension worthy of considerable attention and development. One integration strategy is the constructivist approach called guided inquiry. Pretest-post test control group design was used in order to answer these research questions. Post test scores in the environmental education items of the literacy test suggested that the use of the guided inquiry integration model improves students' environmental literacy. The environmental-related behavior/practices, focus group interview and researcher's recorded observations support positive effect of the approach.